Positive electrode active material and preparation method thereof, secondary battery and electric device
By designing a lithium-rich layer structure in the positive electrode active material, the problems of unstable structure and capacity attenuation of lithium-rich ternary positive electrode material during charging and discharging are solved, and the high energy density and excellent cycling and safety performance of the battery are achieved.
Patent Information
- Application Number
- CN202211525557.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-01
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-12-01
AI Technical Summary
The lithium-rich ternary cathode material has problems such as structural instability, oxygen precipitation and capacity attenuation during charging and discharging, which limits its further development.
The positive electrode active material with a lithium-rich layer structure is Li1+a[NixCoyMnzM1bM2c]O2, and is prepared by low temperature coheating and water washing, forming a lithium-rich layer extending from the surface of the particles to the inside to improve structural stability and Compact density.
The energy density, cycle performance and safety performance of the battery are improved, and the service life of the battery is extended by maintaining the layered structure, inhibiting inter-layer migration of Ni and reducing oxygen release.
Smart Images

Figure CN115863571B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium batteries, and in particular to a positive electrode active material and a preparation method thereof, and a secondary battery and an electrical device comprising the positive electrode active material. Background Art
[0002] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion batteries have made great progress, higher requirements have been put forward for their energy density, cycle performance and safety performance.
[0003] Positive electrode materials are an important component of lithium-ion batteries. They not only affect the safety and cost of batteries, but are also the key factors that directly determine the electrochemical performance and life of batteries. At present, common positive electrode materials include layered structure materials (such as lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, etc.), spinel structure materials, polyanion materials, and ternary materials. Among them, layered lithium-rich ternary positive electrode materials are a type of positive electrode material that has attracted much attention in recent years. They have high discharge capacity (>250mA·h / g), energy density (above 300Wh / kg), working voltage range (3.7-4.8V), low cost and environmental friendliness. They are generally considered to be one of the best choices for the next generation of battery positive electrode materials. However, due to the structural instability of lithium-rich ternary positive electrode materials themselves, there will be serious problems such as layered structure destruction, oxygen precipitation and capacity attenuation during the charge and discharge process. These problems in the charge and discharge process have hindered the further development of lithium-rich ternary positive electrode materials to a certain extent. Therefore, certain strategies need to be adopted to optimize lithium-rich ternary positive electrode materials, so as to improve the structural stability of lithium-rich ternary materials, inhibit voltage attenuation, and inhibit side reactions with the electrolyte. Summary of the invention
[0004] The present application is made in view of the above-mentioned problems, and its purpose is to provide a positive electrode active material with improved structural stability and high compaction density, and to provide a preparation method of the positive electrode active material, as well as a positive electrode sheet, a secondary battery and an electrical device containing the positive electrode active material of the present application.
[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides a positive electrode active material, characterized in that the chemical formula of the positive electrode active material is Li 1+a [Ni x Co y Mn z M1 b M2 cO2, where 0.05 < a < 0.5, 1 / 3 ≤ x < 1, 0 ≤ y < 1 / 3, 0 ≤ z < 1 / 3, 0 < b < 0.1, 0 < c < 0.1, x + y + z + b + c = 1, M1 is one or more elements selected from Mo, Zr, W, Sb, Nb, Te, and Ga, M2 is one or more elements selected from Mg, Al, Ca, and Ti. Optionally, 0.1 < a < 0.2, 0.6 ≤ x < 1,
[0006] The positive electrode active material is in a particulate shape and includes a lithium-rich layer extending from the particle surface into the particle interior. In a single particle of the positive electrode active material, on a cross-section passing through the geometric center of the particle, the ratio of the average Li element content per unit area in the lithium-rich layer to the average Li element content per unit area in the non-lithium-rich layer is (>1 - 1.5):1, optionally (1.05 - 1.2):1.
[0007] Thus, compared with the prior art, the present application at least includes the following beneficial effects:
[0008] (1) The positive electrode active material of the present application not only has a high tap density, can effectively improve the energy density of the battery, but also has improved structural stability, effectively preventing side reactions of the electrolyte on the surface of the positive electrode active material, thereby improving the cycle performance and safety performance of the battery;
[0009] (2) The positive electrode active material of the present application has a lithium-rich layer. During charge and discharge, on the one hand, it is beneficial to maintain a stable layered structure of the positive electrode active material, and on the other hand, it is beneficial to promote the in-layer migration of Ni and inhibit the inter-layer migration of Ni, effectively reducing the degree of lithium-nickel mixing. At the same time, the vacancy clusters formed by the migration of Ni can fix the activated lattice oxygen, reduce oxygen release, thereby improving the cycle performance and safety performance of the battery.
[0010] In any embodiment, the positive electrode active material satisfies: k = 2t / Dv50, and k is greater than 0 to 0.6, optionally 0.01 to 0.3, where t is the thickness of the lithium-rich layer extending from the particle surface of the positive electrode active material into the particle interior, and Dv50 is the particle size corresponding to when the volume cumulative distribution percentage of the positive electrode active material reaches 50%. When the positive electrode active material satisfies the above formula, the positive electrode active material has good structural stability, and the lithium-rich layer structure of the positive electrode active material can maintain a stable layered structure during charge and discharge, inhibit the inter-layer migration of Ni, reduce oxygen release, thereby improving the cycle performance and safety performance of the battery.
[0011] In any embodiment, the Dv50 of the positive electrode active material is 5-15 μm, optionally 8-10 μm. When the Dv50 of the positive electrode active material is within the above range, the positive electrode active material has good structural stability, and the lithium-rich layer structure of the positive electrode active material can maintain a stable layered structure during charge and discharge, inhibit the interlayer migration of Ni, reduce oxygen release, thereby improving the cycle performance and safety performance of the battery.
[0012] In any embodiment, the degree of lithium-nickel mixing of the positive electrode active material is ≤5%, optionally ≤3%. The lithium-rich layer structure of the positive electrode active material of the present application effectively reduces the degree of lithium-nickel mixing of the positive electrode active material and maintains the stability of the layered structure, thereby improving the cycle performance and safety performance of the battery.
[0013] In any embodiment, the weight ratio of M1 element to M2 element in the positive electrode active material is 1:0.1-1:1, optionally 1:0.1-1:0.5. When the weight ratio of M1 element to M2 element in the positive electrode active material satisfies the above range, the structural stability of the material can be improved, thereby improving the cycle performance and safety performance of the battery.
[0014] In any embodiment, the positive electrode active material further has a coating, and the chemical formula of the coating is Li e CoO2, where 0 < e ≤ 1. The coating Li e CoO2 can effectively prevent side reactions of the electrolyte on the surface of the positive electrode active material, reduce oxygen release, thereby further improving the cycle performance and safety performance of the battery.
[0015] In any embodiment, the thickness of the coating is 0.01-0.2 μm, optionally 0.05-0.1 μm. When the thickness of the coating is within the above range, it can effectively prevent side reactions of the electrolyte on the surface of the positive electrode active material, thereby further improving the cycle performance and safety performance of the battery.
[0016] In any embodiment, the weight ratio of the coating to the positive electrode active material is (0.002-0.02):1, optionally (0.005-0.012):1. When the weight ratio of the coating to the positive electrode active material satisfies the above range, the cycle performance and safety performance of the battery are effectively improved.
[0017] In any embodiment, (Dv90-Dv10) / Dv50 of the positive electrode active material is ≥1.1, optionally ≥1.2. When the positive electrode active material satisfies the above range, the inter-particle filling degree is high, it has good dispersibility, and can effectively improve the energy density of the battery.
[0018] In any embodiment, the tap density of the positive electrode active material under a pressure of 5000 kg / 1.33 cm 2 is ≥ 3.4 g / cm 3 . The positive electrode active material has a high tap density, which can effectively improve the energy density of the battery.
[0019] The second aspect of the present application provides a method for preparing a positive electrode active material, the method comprising the following steps:
[0020] S1) Low-temperature co-heating the precursor of the positive electrode active material and a lithium source to obtain a mixture, mixing the mixture with a compound containing M1 element and a compound containing M2 element, and sintering to obtain a matrix material;
[0021] S2) Adding the matrix material obtained in step S1) to an aqueous solution containing a soluble Co-containing compound and a soluble Li-containing compound for water washing, filtering, and drying to obtain the positive electrode active material;
[0022] Wherein, in the step S1), the temperature of the low-temperature co-heating is 150 - 400 °C, optionally 200 - 300 °C, and the time is 1 - 6 h, optionally 2 - 4 h,
[0023] The chemical formula of the positive electrode active material is Li 1+a [Ni x Co y Mn z M1 b M2 c O2, wherein, 0.05 < a < 0.5, 1 / 3 ≤ x < 1, 0 ≤ y < 1 / 3, 0 ≤ z < 1 / 3, 0 < b < 0.1, 0 < c < 0.1, x + y + z + b + c = 1, M1 is one or more elements selected from Mo, Zr, W, Sb, Nb, Te, and Ga, M2 is one or more elements selected from Mg, Al, Ca, and Ti, optionally, 0.1 < a < 0.2, 0.6 ≤ x < 1,
[0024] The positive electrode active material is in the shape of particles, including a lithium-rich layer extending from the particle surface to the particle interior. In a single particle of the positive electrode active material, on a cross-section passing through the geometric center of the particle, the ratio of the average Li element content per unit area in the lithium-rich layer to the average Li element content per unit area in the non-lithium-rich layer is (>1 - 1.5):1, optionally (1.05 - 1.2):1.
[0025] Therefore, the positive electrode active material with a lithium-rich layer structure prepared by the above method not only has a high compaction density, which can effectively improve the energy density of the battery, but also has improved structural stability, effectively preventing the electrolyte from having side reactions on the surface of the positive electrode active material, thereby improving the battery's cycle performance and safety performance.
[0026] In any embodiment, in the step S1), the molar ratio of the Li element in the lithium source to the metal element in the precursor of the positive electrode active material is 1.2-1.5, optionally 1.25-1.4, the metal elements are Ni, Co and Mn, the sintering temperature is 600-850°C, the sintering time is 9-12h, and the sintering atmosphere is air or oxygen, optionally oxygen. By regulating the above parameters, the obtained positive electrode active material can have a high compaction density and improved structural stability.
[0027] In any embodiment, in the step S1), the compound containing the M1 element is one or more of the oxide, hydroxide, carbonate, oxalate or nitrate containing the M1 element, and the amount of the M1 element added in the step S1) is 2000-5000ppm, optionally 3000-4000ppm, based on the weight of the precursor of the positive active material; the compound containing the M2 element is one or more of the oxide, hydroxide, carbonate, oxalate or nitrate containing the M2 element, and the amount of the M2 element added in the step S1) is 200-2000ppm, optionally 400-1000ppm, based on the weight of the precursor of the positive active material. By regulating the above parameters, the obtained positive active material can have improved structural stability, thereby improving the cycle performance and safety performance of the battery.
[0028] In any embodiment, in the step S2), the soluble Co-containing compound is selected from one or more of Co(CH3COO)2, CoC2O4, CoSO4, Co(NO3)2 and CoCl2, and the amount of Co element added in the step S2) is 1000-20000ppm, optionally 5000-13000ppm, based on the weight of the precursor of the positive active material; the soluble Li-containing compound is selected from one or more of Li2SO4, LiNO3, LiC2O4, CH3COOLi and LiCl, and the amount of Li element added in the step S2) is 500-5000ppm, optionally 1000-1500ppm, based on the weight of the precursor of the positive active material. By regulating the above parameters, a positive active material with a lithium-rich layer structure can be obtained, thereby improving the cycle performance and safety performance of the battery.
[0029] In any embodiment, in step S2), the temperature of the water washing is 0 - 100 °C, optionally 5 - 50 °C, and the time of the water washing is 1 - 30 min, optionally 2 - 5 min. By regulating the above parameters, a cathode active material with a lithium-rich layer structure can be obtained, thereby improving the cycle performance and safety performance of the battery.
[0030] In any embodiment, in step S2), the drying is vacuum drying, and the drying temperature is 40 - 120 °C, optionally 80 - 100 °C, and the drying time is 6 - 24 h, optionally 12 - 18 h.
[0031] In any embodiment, in step S1), the lithium source is selected from at least one of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4, and CH3COOLi, optionally at least one of LiOH·H2O, Li2SO4, and LiNO3.
[0032] In any embodiment, the method further includes step S3): mixing the cathode active material obtained in step S2) with a Co-containing compound and a Li-containing compound, the sintering temperature is 500 - 800 °C, optionally 550 - 750 °C, the sintering time is 5 - 15 h, optionally 5 - 10 h, and the sintering atmosphere is air or O2, to obtain a cathode active material with a coating, and the chemical formula of the coating is Li e CoO2, where 0 < e ≤ 1. By regulating the above parameters, a coating layer can be formed on the cathode active material, effectively preventing side reactions of the electrolyte on the surface of the cathode active material, reducing oxygen evolution, and further improving the cycle performance and safety performance of the battery.
[0033] In any embodiment, in the step S3), the Co-containing compound is selected from at least one of Co3O4, Co(OH)2, CoO, CoOOH, Co(CH3COO)2, CoC2O4 and CoCO3, the Dv50 of the Co-containing compound particles is 0.001-10 μm, optionally 0.001-1 μm, the amount of Co element added in the step S3) is 500-20000 ppm, optionally 2000-15000 ppm, based on the positive electrode The weight of the precursor of the active material; the Li-containing compound is selected from at least one of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4 and CH3COOLi, the Dv50 of the Li-containing compound particles is 0.001-1μm, optionally 0.01-0.05μm, and the amount of Li element added in the step S3) is 100-3000ppm, optionally 500-1500ppm, based on the weight of the precursor of the positive active material. By regulating the above parameters, a coating layer can be formed on the positive active material, effectively preventing the electrolyte from having side reactions on the surface of the positive active material, reducing oxygen release, and further improving the cycle performance and safety performance of the battery.
[0034] The third aspect of the present application provides a secondary battery, which includes the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared by the method of the second aspect of the present application or the positive electrode plate of the third aspect of the present application.
[0035] A fourth aspect of the present application provides an electrical device, which includes a secondary battery selected from the fourth aspect of the present application.
[0036] The electric device of the present application includes the secondary battery provided by the present application, and thus has at least the same advantages as the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 is a schematic diagram of a secondary battery according to one embodiment of the present application.
[0038] Figure 2 yes Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.
[0039] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0040] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0041] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0042] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.
[0043] Description of reference numerals:
[0044] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 top cover assembly DETAILED DESCRIPTION
[0045] Below, the embodiments of the positive electrode active material and preparation method thereof, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0046] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0047] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0048] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0049] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0050] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0051] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0052] Layered lithium-rich ternary cathode materials have attracted much attention due to their high discharge capacity and operating voltage range. However, there are still many problems with lithium-rich ternary cathode materials. For example, due to the Ni 2+ The radius (R Ni 2+ =0.069nm) and Li + The radius (R Li +=0.076nm) is very close, so the Ni in the transition metal layer 2+ It is easy to migrate to the lithium layer and occupy the Li + The location of Li + The transmission of Li +It cannot be embedded in the lattice, resulting in a reduction in the reversible specific capacity and a decrease in the Coulombic efficiency; during the cycling process of the lithium-rich ternary cathode material, some transition metals will transfer to the tetrahedral interstitial sites, so the material structure will transform into spinel, leading to voltage decay; the layered lithium-rich ternary cathode material is prone to causing electrolyte decomposition at a high cut-off voltage (>4.6 V), resulting in poor cycling performance. Currently, the electrochemical performance of the material is usually improved by means such as surface coating and ion doping. However, it is still necessary to continuously improve the preparation process and modification means to enhance the structural stability of the lithium-rich ternary material, inhibit voltage decay, and inhibit its side reactions with the electrolyte, etc., so as to obtain a lithium-rich ternary cathode material with excellent performance.
[0053] In view of the above problems, the present application provides a cathode active material, characterized in that the chemical formula of the cathode active material is Li 1+a [Ni x Co y Mn z M1 b M2 c O2, where 0.05 < a < 0.5, 1 / 3 ≤ x < 1, 0 ≤ y < 1 / 3, 0 ≤ z < 1 / 3, 0 < b < 0.1, 0 < c < 0.1, x + y + z + b + c = 1, M1 is one or more elements selected from Mo, Zr, W, Sb, Nb, Te, and Ga, M2 is one or more elements selected from Mg, Al, Ca, and Ti. Optionally, 0.1 < a < 0.2, 0.6 ≤ x < 1,
[0054] The cathode active material is in the shape of particles and includes a lithium-rich layer extending from the particle surface to the particle interior. In a single particle of the cathode active material, on a cross-section passing through the geometric center of the particle, the ratio of the average Li element content per unit area in the lithium-rich layer to the average Li element content per unit area in the non-lithium-rich layer is (>1 - 1.5):1, and can be optionally (1.05 - 1.2):1.
[0055] Although the mechanism is not clear, the applicant unexpectedly found that: it not only has a high compaction density, which can effectively improve the energy density of the battery, but also has improved structural stability, effectively preventing the electrolyte from having side reactions on the surface of the positive electrode active material, thereby improving the battery's cycle performance and safety performance. Specifically, on the one hand, the positive electrode active material has a lithium-rich layer structure, which can maintain a stable layered structure of the positive electrode active material during the charge and discharge process, promote Ni to migrate within the layer, and effectively reduce the degree of lithium-nickel mixing. At the same time, the vacancy clusters formed by Ni migration can fix the activated lattice oxygen and reduce oxygen release, thereby improving the battery's cycle performance and safety performance; on the other hand, the M1 and M2 elements doped in the positive electrode active material can stabilize the lattice structure, effectively improve the structural stability of the positive electrode active material, thereby further improving the battery's cycle performance and safety performance.
[0056] In some embodiments, the ratio of the average Li content per unit area in the lithium-rich layer to the average Li content per unit area in the non-lithium-rich layer is, for example, at least 1.01: 1, at least 1.05: 1, at least 1.1: 1, at least 1.18: 1, at least 1.2: 1, at least 1.3: 1, at least 1.4: 1 or at least 1.5: 1. In the present application, the Li content and distribution change in the positive electrode active material can be obtained by using the technology commonly used to detect the Li content known in the art, for example, using the PHI NanoTOFII time-of-flight secondary mass spectrometer of Ulvac-Phi Company of Japan to obtain the Li content and distribution change in the material.
[0057] In some embodiments, the positive electrode active material satisfies: k=2t / Dv50, and k is greater than 0 to 0.6, and can be optionally 0.01 to 0.3, wherein t is the thickness of the lithium-rich layer extending from the particle surface of the positive electrode active material to the interior of the particle, and the Dv50 is the particle size corresponding to when the volume cumulative distribution percentage of the positive electrode active material reaches 50%. When the positive electrode active material satisfies the above formula, the positive electrode active material has good structural stability, and the lithium-rich layer structure of the positive electrode active material can maintain a stable layered structure during the charge and discharge process, inhibit the interlayer migration of Ni, and reduce oxygen release, thereby improving the cycle performance and safety performance of the battery. In other embodiments, the k is, for example, greater than 0.001, greater than 0.01, greater than 0.08, greater than 0.1, greater than 0.2, greater than 0.3, greater than 0.4, greater than 0.5 or greater than 0.6.
[0058] In the present application, the thickness t of the lithium-rich layer extending from the particle surface of the positive electrode active material to the interior of the particle is, for example, greater than 0.00475 μm, greater than 0.0475 μm, greater than 0.38 μm, greater than 0.95 μm, greater than 1.425 μm, greater than 1.9 μm or greater than 2.85 μm.
[0059] In some embodiments, the Dv50 of the positive electrode active material is 5-15 μm, optionally 8-10 μm. When the Dv50 of the positive electrode active material is within the above range, the positive electrode active material has good structural stability, and the lithium-rich layer structure of the positive electrode active material can maintain a stable layered structure during the charge and discharge process, inhibit the interlayer migration of Ni, and reduce oxygen release, thereby improving the cycle performance and safety performance of the battery.
[0060] In some embodiments, the lithium-nickel mixing degree of the positive electrode active material is ≤5%, optionally ≤3%. In other embodiments, the lithium-nickel mixing degree of the positive electrode active material is, for example, ≤5%, ≤4%, ≤3.5%, ≤3%, ≤2.5%, ≤2%, ≤1.5% or ≤1%. 2+ The radius and Li + The radius is very close, so the Ni in the transition metal layer 2+ It is easy to migrate to the lithium layer and occupy the site of lithium, causing cation mixing (i.e., lithium-nickel mixing), resulting in poor structural stability of the positive electrode active material. The performance of the positive electrode active material decreases as the degree of cation mixing increases. However, the lithium-rich layer structure of the positive electrode active material of the present application can promote Ni to migrate within the layer and inhibit its interlayer migration, effectively reduce the degree of lithium-nickel mixing, maintain the stability of the layered structure, and at the same time, the vacancy clusters formed by Ni migration can fix the activated lattice oxygen and reduce oxygen release, thereby improving the cycle performance and safety performance of the battery.
[0061] In the present application, the XRD pattern of the positive electrode active material can be obtained by using a D8 Advance X-ray diffractometer (XRD) of Bruker Corporation of Germany, and the lithium-nickel mixing degree value of the positive electrode active material can be obtained by open source software (ie, GSAS software).
[0062] In some embodiments, the weight ratio of the M1 element to the M2 element in the positive electrode active material is 1:0.1-1:1, optionally 1:0.1-1:0.5. When the weight ratio of the M1 element to the M2 element in the positive electrode active material satisfies the above range, the structural stability of the material can be improved, thereby improving the cycle performance and safety performance of the battery. In the present application, the amount of the M1 element and the M2 element is measured by a detection technique commonly used to measure the content of doping elements known in the art, such as inductively coupled plasma emission spectroscopy (ICP).
[0063] In some embodiments, the positive electrode active material further has a coating, and the chemical formula of the coating is Li e CoO2, where 0 < e ≤ 1. The coating Li e CoO2 can effectively prevent side reactions of the electrolyte on the surface of the positive electrode active material, reduce oxygen release, and thus further improve the cycle performance and safety performance of the battery.
[0064] In some embodiments, the thickness of the coating is 0.01 - 0.2 μm, optionally 0.05 - 0.1 μm. When the thickness of the coating is within the above range, side reactions of the electrolyte on the surface of the positive electrode active material can be effectively prevented, thereby further improving the cycle performance and safety performance of the battery.
[0065] In some embodiments, the weight ratio of the coating to the positive electrode active material is (0.002 - 0.02):1, optionally (0.005 - 0.012):1. When the weight ratio of the coating to the positive electrode active material meets the above range, the cycle performance and safety performance of the battery are effectively improved.
[0066] In some embodiments, (Dv90 - Dv10) / Dv50 of the positive electrode active material is ≥ 1.1, optionally ≥ 1.2. When the positive electrode active material meets the above range, the inter-particle packing density is high, it has good dispersibility, and can effectively improve the energy density of the battery.
[0067] In the present application, Dv10, Dv50, and Dv90 are the particle sizes of the positive electrode active material measured by volume particle size distribution, where Dv10 is the particle size corresponding to when the cumulative volume percentage of the sample reaches 10%, Dv50 is the particle size corresponding to when the cumulative volume percentage of the sample reaches 50%, and Dv90 is the particle size corresponding to when the cumulative volume percentage of the sample reaches 90%.
[0068] In some embodiments, the tap density of the positive electrode active material under a pressure of 5000 kg / 1.33 cm 2 is ≥ 3.4 g / cm 3 . The positive electrode active material has a high tap density, which can effectively improve the energy density of the battery. The tap density can be measured according to GB / T 24533 - 2009.
[0069] The second aspect of the present application provides a method for preparing a positive electrode active material, and the method includes the following steps:
[0070] S1) Low-temperature co-heating the precursor of the positive electrode active material and a lithium source to obtain a mixture, mixing the mixture with a compound containing M1 element and a compound containing M2 element, and sintering to obtain a matrix material;
[0071] S2) Add the matrix material obtained in step S1) to an aqueous solution containing a soluble Co-containing compound and a soluble Li-containing compound for water washing, filtration, and drying to obtain a positive electrode active material;
[0072] Among them, in the said step S1), the temperature of the low-temperature co-heating is 150 - 400 °C, optionally 200 - 300 °C, and the time is 1 - 6 h, optionally 2 - 4 h.
[0073] The chemical formula of the positive electrode active material is Li 1+a [Ni x Co y Mn z M1 b M2 c O2, where 0.05 < a < 0.5, 1 / 3 ≤ x < 1, 0 ≤ y < 1 / 3, 0 ≤ z < 1 / 3, 0 < b < 0.1, 0 < c < 0.1, x + y + z + b + c = 1, M1 is one or more elements selected from Mo, Zr, W, Sb, Nb, Te, and Ga, and M2 is one or more elements selected from Mg, Al, Ca, and Ti. Optionally, 0.1 < a < 0.2, 0.6 ≤ x < 1.
[0074] The positive electrode active material is in the shape of particles and includes a lithium-rich layer extending from the particle surface to the particle interior. In a single particle of the positive electrode active material, on the cross-section passing through the geometric center of the particle, the ratio of the average Li element content per unit area in the lithium-rich layer to the average Li element content per unit area in the non-lithium-rich layer is (>1 - 1.5):1, optionally (1.05 - 1.2):1.
[0075] Thus, the positive electrode active material with a lithium-rich layer structure prepared by the above method not only has a high tap density, can effectively improve the energy density of the battery, but also has improved structural stability, effectively preventing side reactions of the electrolyte on the surface of the positive electrode active material, thereby improving the cycle performance and safety performance of the battery.
[0076] In this application, the preparation of the precursor of the positive electrode active material can be obtained by a method known in the prior art, such as the hydroxide co-precipitation method, for example, by the method described in CN 111384372A. More specifically, the precursor of the first positive electrode active material A may include, but is not limited to, Ni 0.8 Co 0.1 Mn 0.1 (OH)2, Ni 0.9 Co 0.05 Mn 0.05 (OH)2, Ni 0.7 Co 0.1Mn 0.2 (OH)2、Ni 0.96 Co 0.03 Mn 0.01 (OH)2、Ni 0.75 Co 0.1 Mn 0.15 (OH)2. The precursor of the second positive electrode active material B may include but is not limited to Ni 0.8 Co 0.1 Mn 0.1 (OH)2、Ni 0.9 Co 0.05 Mn 0.05 (OH)2、Ni 0.7 Co 0.1 Mn 0.2 (OH)2、Ni 0.96 Co 0.03 Mn 0.01 (OH)2、Ni 0.75 Co 0.1 Mn 0.15 (OH)2.
[0077] In some embodiments, in the step S1), the low temperature heating temperature is, for example, 200-250°C.
[0078] In some embodiments, in the step S1), the molar ratio of the Li element in the lithium source to the metal element in the precursor of the positive electrode active material is 1.2-1.5, and optionally 1.25-1.4, the metal elements are Ni, Co and Mn, the sintering temperature is 600-850°C, the sintering time is 9-12h, and the sintering atmosphere is air or oxygen, and optionally oxygen. The molar ratio of the Li element to the metal element in the precursor, the sintering temperature and the sintering time can make the obtained positive electrode active material have a high compaction density and improved structural stability.
[0079] In some embodiments, in the step S1), the compound containing the M1 element is one or more of an oxide, hydroxide, carbonate, oxalate or nitrate containing the M1 element, and the amount of the M1 element added in the step S1) is 2000-5000ppm, optionally 3000-4000ppm, based on the weight of the precursor of the positive active material; the compound containing the M2 element is one or more of an oxide, hydroxide, carbonate, oxalate or nitrate containing the M2 element, and the amount of the M2 element added in the step S1) is 200-2000ppm, optionally 400-1000ppm, based on the weight of the precursor of the positive active material. By selecting the sources of the M1 element and the M2 element and regulating their respective contents, the obtained positive active material can have improved structural stability, thereby improving the cycle performance and safety performance of the battery.
[0080] In some embodiments, in the step S2), the soluble Co-containing compound is selected from one or more of Co(CH3COO)2, CoC2O4, CoSO4, Co(NO3)2 and CoCl2, and the amount of Co element added in the step S2) is 1000-20000ppm, optionally 5000-13000ppm, based on the weight of the precursor of the positive electrode active material; the soluble Li-containing compound is selected from one or more of Li2SO4, LiNO3, LiC2O4, CH3COOLi and LiCl, and the amount of Li element added in the step S2) is 500-5000ppm, optionally 1000-1500ppm, based on the weight of the precursor of the positive electrode active material. By selecting a soluble Co-containing compound and regulating the amount of the added Co element and selecting a soluble Li-containing compound and regulating the amount of the added Li element, a positive electrode active material with a lithium-rich layer structure can be obtained, thereby improving the cycle performance and safety performance of the battery.
[0081] In some embodiments, in step S2), the water washing temperature is 0-100°C, optionally 5-50°C, and further optionally 10-30°C, and the water washing time is 1-30min, optionally 2-5min. By adjusting the water washing temperature and time in step S2), a positive electrode active material with a lithium-rich layer structure can be obtained, thereby improving the cycle performance and safety performance of the battery.
[0082] In some embodiments, in step S2), the drying is vacuum drying, and the drying temperature is 40-120° C., optionally 80-100° C., and the drying time is 6-24 hours, optionally 12-18 hours.
[0083] In some embodiments, in step S1), the lithium source is selected from at least one of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4, and CH3COOLi, and may be optionally at least one of LiOH·H2O, Li2SO4, and LiNO3.
[0084] In some embodiments, the method further includes step S3): mixing the cathode active material obtained in step S2) with a Co-containing compound and a Li-containing compound, with a sintering temperature of 500 - 800 °C, optionally 550 - 750 °C, a sintering time of 5 - 15 h, optionally 5 - 10 h, and a sintering atmosphere of air or O2, to obtain a cathode active material with a coating, and the chemical formula of the coating is Li e CoO2, where 0 < e ≤ 1. By adding a Co-containing compound and a Li-containing compound, a coating layer can be formed on the cathode active material, and this coating layer can effectively prevent side reactions of the electrolyte on the surface of the cathode active material, reduce oxygen release, and thus further improve the cycle performance and safety performance of the battery.
[0085] In some embodiments, in step S3), the Co-containing compound is selected from at least one of Co3O4, Co(OH)2, CoO, CoOOH, Co(CH3COO)2, CoC2O4, and CoCO3, the Dv50 of the Co-containing compound particles is 0.001 - 10 μm, optionally 0.001 - 1 μm, and the amount of Co element added in step S3) is 500 - 20000 ppm, optionally 2000 - 15000 ppm, based on the weight of the precursor of the cathode active material; the Li-containing compound is selected from at least one of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4, and CH3COOLi, the Dv50 of the Li-containing compound particles is 0.001 - 1 μm, optionally 0.01 - 0.05 μm, and the amount of Li element added in step S3) is 100 - 3000 ppm, optionally 500 - 1500 ppm, based on the weight of the precursor of the cathode active material. By regulating the above parameters, a coating layer can be formed on the cathode active material, effectively preventing side reactions of the electrolyte on the surface of the cathode active material, reducing oxygen release, and thus further improving the cycle performance and safety performance of the battery.
[0086] The third aspect of the present application provides a positive electrode plate, which includes a positive electrode collector and a positive electrode film layer arranged on at least one surface of the positive electrode collector, the positive electrode film layer includes the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared by the method of the second aspect of the present application, and the content of the positive electrode active material in the positive electrode film layer is more than 10 weight%, based on the total weight of the positive electrode film layer.
[0087] The fourth aspect of the present application provides a secondary battery, which includes the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared by the method of the second aspect of the present application or the positive electrode plate of the third aspect of the present application.
[0088] A fifth aspect of the present application provides an electrical device, which includes a secondary battery selected from the fourth aspect of the present application.
[0089] In the present application, the secondary battery may be in the form of a battery cell, a battery module, or a battery pack. The battery module and the battery pack may include a battery cell, and the battery pack may also include a battery module.
[0090] In some embodiments, the battery cells may be assembled into a battery module. In some embodiments, the battery cells may be assembled into a battery pack. In some embodiments, the battery modules may be assembled into a battery pack.
[0091] In addition, the secondary battery (in the form of a battery cell), a battery module, a battery pack, and an electric device of the present application are described below with reference to the drawings as appropriate.
[0092] In one embodiment of the present application, a secondary battery is provided.
[0093] Typically, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through. In this application, the battery group margin is 90-95%.
[0094] [Positive electrode]
[0095] The positive electrode sheet includes a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material of the first aspect of the present application.
[0096] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0097] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0098] In some embodiments, the positive electrode active material may be the positive electrode active material of the first aspect of the present application. The weight ratio of the positive electrode active material in the positive electrode film layer is 80-100 weight %, based on the total weight of the positive electrode film layer.
[0099] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.
[0100] In some embodiments, the positive electrode film layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.
[0101] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; wherein the positive electrode slurry has a solid content of 40-80wt%, and the viscosity at room temperature is adjusted to 5000-25000mPa·s, and the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, a positive electrode sheet can be obtained, and the positive electrode powder coating unit surface density is 150-350mg / m 2 The compaction density of the positive electrode is 3.0-3.6g / cm 3 , optional: 3.3-3.5g / cm 3 The calculation formula of the compacted density is:
[0102] Compacted density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).
[0103] [Negative electrode]
[0104] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0105] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0106] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0107] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The negative electrode active material may have an average particle size (D 10 ), having an average particle size (D 50 ), and having an average particle size (D) of 26 μm to 40 μm, preferably 30 μm to 37 μm 90 ). 10 D is the particle size corresponding to the cumulative volume distribution percentage of the sample reaching 10%; 50 D is the particle size corresponding to the cumulative volume distribution percentage of the sample reaching 50%; 90The particle size corresponding to the cumulative volume distribution percentage of the sample reaches 90%. The weight ratio of the negative electrode active material in the negative electrode film layer is 70-100 weight %, based on the total weight of the negative electrode film layer.
[0108] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0-30% by weight, based on the total weight of the negative electrode film layer.
[0109] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0-20 weight %, based on the total weight of the negative electrode film layer.
[0110] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)), etc. The weight ratio of the other additives in the negative electrode film layer is 0-15% by weight, based on the total weight of the negative electrode film layer.
[0111] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30-70wt%, and the viscosity at room temperature is adjusted to 2000-10000mPa·s; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The negative electrode powder coating unit area density is 75-220mg / m 2 , the compaction density of negative electrode is 1.2-2.0g / m 3 .
[0112] [Electrolytes]
[0113] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0114] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0115] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorobis(oxalatophosphate) and lithium tetrafluorooxalatophosphate. The concentration of the electrolyte salt is generally 0.5-5 mol / L.
[0116] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0117] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0118] [Isolation film]
[0119] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0120] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0121] In some embodiments, the isolation film has a thickness of 6-40 μm, and optionally 12-20 μm.
[0122] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator may be formed into an electrode assembly by a winding process or a lamination process.
[0123] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0124] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0125] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.
[0126] In some embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0127] In some embodiments, secondary batteries may be assembled into a battery module. The number of secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.
[0128] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.
[0129] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0130] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.
[0131] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0132] In addition, the present application also provides an electrical device, which includes at least one of the secondary battery, battery module, or battery pack provided in the present application. The secondary battery, battery module, or battery pack can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.
[0133] As the electrical device, a secondary battery, a battery module or a battery pack may be selected according to its usage requirements.
[0134] Figure 6 The power consumption device is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the power consumption device for the secondary battery, a battery pack or a battery module can be used.
[0135] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.
[0136] Example
[0137] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0138] 1. Preparation of secondary batteries
[0139] Example 1
[0140] 1. Preparation of positive electrode active materials
[0141] 1) Preparation of precursors of positive electrode active materials
[0142] Nickel sulfate, cobalt sulfate and manganese sulfate were prepared into a 2 mol / L metal salt solution in a molar ratio of 9:0.5:0.5, and then the metal salt solution, 8 mol / L ammonia water and 5 mol / L NaOH solution were continuously added into a reactor for reaction. The precursor of the positive electrode active material (Ni 2O3) was prepared by a hydroxide coprecipitation method by controlling the pH value of the reaction process to 11.30, the ammonia concentration to 4.0 g / L, the reaction time to 20 h, and the stirring rate to 300 r / min. 0.9 Co 0.05 Mn 0.05 (OH)2), particle size Dv50 is 9.5μm.
[0143] 2) Preparation of positive electrode active materials
[0144] S1) lithium hydroxide and the precursor of the positive electrode active material prepared above are co-heated at 250° C. for 3 h at a molar ratio of Li / Me (Me is the total molar ratio of Ni, Co and Mn) of 1.3:1 to obtain a mixture, and the mixture is placed in a plow mixer with niobium pentoxide (Nb2O5) and aluminum oxide (Al2O3) to mix evenly, wherein the molar ratio of lithium hydroxide, the precursor of the positive electrode active material, Nb2O5, and Al2O3 is 1.3:1:0.0020:0.0036, and then the materials are placed in a kiln for sintering at a sintering temperature of 780° C., a sintering time of 12 h, and an oxygen atmosphere, and after cooling, a matrix material is obtained;
[0145] S2) adding the above-obtained matrix material to an aqueous solution containing cobalt acetate ((CH3COO)2Co) and lithium acetate (CH3COOLi), wherein the amount of Co element is 5000ppm and the amount of Li element is 1000ppm, washing with water at 10°C for 3min, filtering, and then drying in a vacuum drying oven at 105°C for 24h, cooling, and mechanically crushing to obtain the positive electrode active material Li 1.15 Ni 0.895 0Co 0.0497 Mn 0.0497 Nb 0.002 Al 0.0036 O2, particle size Dv50 is 9.5μm.
[0146] 2. Preparation of button cells
[0147] [Positive electrode sheet] The positive electrode active material, polyvinylidene fluoride (PVDF), and acetylene black obtained above were added to N-methylpyrrolidone (NMP) at a weight ratio of 90:5:5, and stirred in a drying room to form a slurry. The slurry was coated on aluminum foil, dried, and cold pressed to form a positive electrode sheet. The coating amount was 0.01g / cm 2 , compacted density is 3.5g / cm 3 .
[0148] [Negative electrode sheet] Use 0.5mm lithium metal sheet as the negative electrode sheet.
[0149] [Electrolyte] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L.
[0150]
Isolation film
[0151] The isolation membrane was purchased from Cellgard, model number is Cellgard 2400.
[0152] The positive electrode sheet, negative electrode sheet, separator and electrolyte prepared above were assembled into a CR2032 button cell (hereinafter also referred to as "button cell") in a button cell box.
[0153] 3. Preparation of Full Cell
[0154] [Positive electrode sheet] The positive electrode active material obtained above was mixed with acetylene black and polyvinylidene fluoride (PVDF) in a weight ratio of 94:3:3 in N-methylpyrrolidone (NMP), coated on aluminum foil, dried and cold pressed to obtain a positive electrode sheet. The coating amount was 0.176g / cm 2 , compacted density is 3.5g / cm 3 .
[0155] [Negative electrode sheet] Mix the negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) in deionized water at a weight ratio of 90:5:2:2:1, apply it on copper foil, dry it, and cold press it to obtain a negative electrode sheet. The coating amount is 0.124g / cm 2 , compacted density is 1.6g / cm 3 .
[0156] [Electrolyte] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L.
[0157] [Isolation membrane] PE porous polymer film is used as the isolation membrane.
[0158] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrodes to isolate them, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with electrolyte and packaged to obtain a full battery (hereinafter referred to as "full battery"). The length × width × height of the full battery = 90 mm × 30 mm × 60 mm, and the battery group margin is 91.0%.
[0159] Example 2
[0160] The same as Example 1, except that in the preparation of the positive electrode active material, in step S1), the molar ratio of Li / Me is 1.2:1, and in step S2), the amount of Li element added is 1200 ppm.
[0161] Example 3
[0162] The same as Example 1, except that in the preparation of the positive electrode active material, in step S1), the molar ratio of Li / Me is 1.25:1, and in step S2), the amount of Li element added is 1500 ppm.
[0163] Example 4
[0164] The same as Example 1, except that in the preparation of the positive electrode active material, in step S1), the molar ratio of Li / Me is 1.35:1, and in step S2), the amount of Li element added is 1800 ppm.
[0165] Example 5
[0166] The same as Example 1, except that in the preparation of the positive electrode active material, in step S1), the molar ratio of Li / Me is 1.38:1, and in step S2), the amount of Li element added is 2000 ppm.
[0167] Example 6
[0168] The same as Example 1, except that in the preparation of the positive electrode active material, in step S1), the molar ratio of Li / Me is 1.4:1, and in step S2), the amount of Li element added is 2500 ppm.
[0169] Example 7
[0170] The same as Example 1, except that in the preparation of the positive electrode active material, in step S1), the molar ratio of Li / Me is 1.5:1, and in step S2), the amount of Li element added is 3000 ppm.
[0171] Example 8
[0172] The same as Example 1, except that: in the preparation of the positive electrode active material, in step S1), zirconium dioxide (ZrO2) and magnesium sulfate (MgSO4) are used, wherein the amount of Zr element is 2000 ppm and the amount of Mg element is 200 ppm, based on the weight of the precursor of the positive electrode active material; the molar ratio of lithium hydroxide, the precursor of the positive electrode active material, ZrO2, and MgSO4 is 1.3:1:0.0021:0.0008.
[0173] Example 9
[0174] The same as Example 1, except that: in the preparation of the positive electrode active material, in step S1), tungstic acid (H2WO4) and titanium dioxide (TiO2) are used, wherein the amount of W element is 3000 ppm and the amount of Ti element is 1500 ppm, based on the weight of the precursor of the positive electrode active material; the molar ratio of lithium hydroxide, the precursor of the positive electrode active material, H2WO4, and TiO2 is 1.3:1:0.0016:0.0031.
[0175] Example 10
[0176] The same as Example 1, except that: in the preparation of the positive electrode active material, in step S1), molybdenum trioxide (MoO3) and calcium carbonate (CaCO3) are used, wherein the amount of Mo element is 2000 ppm and the amount of Ca element is 2000 ppm, based on the weight of the precursor of the positive electrode active material; the molar ratio of lithium hydroxide, the precursor of the positive electrode active material, MoO3, and CaCO3 is 1.3:1:0.0020:0.0050.
[0177] Embodiment 11
[0178] The same as Example 1, except that: in the preparation of the positive electrode active material, in step S1), the low-temperature co-heating temperature is 200°C.
[0179] Example 12
[0180] The same as Example 1, except that: in the preparation of the positive electrode active material, in step S1), the low-temperature co-heating temperature is 400°C.
[0181] Embodiment 13
[0182] The same as Example 1, except that: in the preparation of the positive electrode active material, in step S2), the water washing temperature is 20° C. and the water washing time is 2 min.
[0183] Embodiment 14
[0184] The same as Example 1, except that: in the preparation of the positive electrode active material, in step S2), the water washing temperature is 30° C. and the water washing time is 1 min.
[0185] Embodiment 15
[0186] The positive electrode active material obtained in Example 1 was mixed with CoOOH and CH3COOLi in a tilted mixer at a weight ratio of 1:0.0140:0.0094, wherein the Dv50 of the CoOOH particles was 0.05 μm, the amount of the Co element was 9000 ppm, the Dv50 of the CH3COOLi particles was 0.01 μm, and the amount of the Li element was 1000 ppm. The materials were then placed in a kiln for sintering at a sintering temperature of 600 ° C, a sintering time of 8 h, and an oxygen atmosphere. After cooling, the coating was Li 0.6 CoO2.
[0187] Example 16
[0188] The same as Example 15, except that the positive electrode active material is mixed with CoOOH and CH3COOLi in an oblique mixer at a weight ratio of 1:0.0023:0.0047, wherein the amount of Co element is 1500 ppm and the amount of Li element is 500 ppm.
[0189] Embodiment 17
[0190] The same as Example 15, except that the positive electrode active material is mixed with CoOOH and CH3COOLi in an oblique mixer at a weight ratio of 1:0.0062:0.0094, wherein the amount of Co element is 4000 ppm and the amount of Li element is 1000 ppm.
[0191] Embodiment 18
[0192] The same as Example 15, except that the positive electrode active material is mixed with CoOOH and CH3COOLi in an oblique mixer at a weight ratio of 1:0.0163:0.0141, wherein the amount of Co element is 10500 ppm and the amount of Li element is 1500 ppm.
[0193] Embodiment 19
[0194] The same as Example 15, except that the positive electrode active material is mixed with CoOOH and CH3COOLi in an oblique mixer at a weight ratio of 1:0.0264:0.0282, wherein the amount of Co element is 17000 ppm and the amount of Li element is 3000 ppm.
[0195] Comparative Example 1
[0196] The preparation of the precursor of the positive electrode active material is the same as that in Example 1.
[0197] The molar ratio of lithium hydroxide, the precursor of the positive electrode active material, Nb2O5, and Al2O3 is 1.05:1:0.0020:0.0036. The materials are then placed in a kiln for sintering at a temperature of 780°C for 12 hours in an oxygen atmosphere. After cooling, the positive electrode active material Li is obtained by mechanical crushing. 1.03 Ni 0.8950 Co 0.0497 Mn 0.0497 Nb 0.002 Al 0.0036 O2, particle size Dv50 is 9.5μm.
[0198] 2. Testing of related parameters
[0199] (1) Particle size test
[0200] The particle size of the positive electrode active material is determined according to GB / T 19077.1-2016 / ISO 13320:2009 (particle size distribution laser diffraction method). Take a clean beaker, add an appropriate amount of the above positive electrode active material, add an appropriate amount of pure water, and ultrasonicate at 120W / 5min to ensure that the material powder is completely dispersed in the water. After the solution is poured into the injection tower of the laser particle size analyzer (Malvern Company, model: Mastersizer3000), it circulates to the test optical path system with the solution. The particles are irradiated by the laser beam, and the particle size distribution characteristics of the particles (shading degree: 8-12%) can be obtained by receiving and measuring the energy distribution of the scattered light, and the corresponding values of Dv10, Dv50, and Dv90 are read.
[0201] The results are shown in Tables 1 and 2.
[0202] (2) Testing of Li element content and distribution changes
[0203] The obtained positive electrode material was mixed with a conductive resin, and after solidification, it was thinned on an ion thinning instrument (instrument company: German Leica, model: RES102). The thinned sample was placed in a time-of-flight secondary mass spectrometer (instrument company: Japanese Ulvac-Phi, model: PHI NanoTOFII). A primary ion source (Bi source) was used to bombard the cut surface of the positive electrode material and excite ions on the cut surface of the material. The ions were collected by an ion collector, and the ion mass M = 6.99 (Li + ) to collect the Li element content and observe the Li element distribution on the cross-section of the positive electrode material.
[0204] The results are shown in Tables 1 and 2.
[0205] (3) Lithium-nickel mixing degree test
[0206] The obtained positive electrode powder material was fully ground and placed on the groove of the XRD diffractometer slide. The slide was placed in the XRD diffractometer (Instrument Company: Bruker, Germany, Model: D8Advance), and the positive electrode material was scanned at a scanning speed of 1° / min to collect the obtained XRD spectrum. The raw data of the XRD spectrum was imported into the GSAS refinement software (open source software), and the XRD spectrum was refined using the Reitveld refinement method, and finally the lithium-nickel mixing degree value was calculated.
[0207] The results are shown in Tables 1 and 2.
[0208] (4) Compaction density test
[0209] Take a certain amount of powder and put it in a special compaction mold, then put the mold on the compaction density instrument. Apply 5000kg (pressing area is 1.33cm 2 )’s pressure, read the thickness of the powder under pressure on the equipment (the thickness after pressure relief), and calculate the compacted density through ρ=m / v.
[0210] The results are shown in Tables 1 and 2.
[0211] 3. Battery performance test
[0212] (1) Initial gram capacity and first efficiency test of button cell
[0213] At 2.8-4.3V, charge the button cell at 0.1C to 4.3V, then charge at a constant voltage at 4.3V to a current ≤0.05mA, let stand for 2min, the charge capacity at this time is recorded as C0, then discharge at 0.1C to 2.8V, the discharge capacity at this time is the initial gram capacity recorded as D0.
[0214] The first effect is calculated according to D0 / C0*100%.
[0215] See Table 3 for the results.
[0216] (2) Fully charged initial gram capacity test
[0217] Under a constant temperature environment of 25℃, let it stand for 5 minutes, discharge to 2.8V at 1 / 3C, let it stand for 5 minutes, charge to 4.25V at 1 / 3C, then charge at constant voltage at 4.25V to a current ≤0.05C, let it stand for 5 minutes, then discharge to 2.8V at 1 / 3C. The discharge capacity at this time is the initial gram capacity, recorded as D0.
[0218] See Table 3 for the results.
[0219] (3) Full battery capacity retention at 25°C
[0220] At 25 °C, charge at a constant current of 1C to 4.25V, then charge at a constant voltage of 4.25V until the current drops to 0.05C, and then discharge at a constant current of 1C to 2.8V to obtain the initial cycle discharge specific capacity (C d1 ); Repeat the charge and discharge process until the 300th cycle. The discharge specific capacity of the lithium-ion battery after n cycles is denoted as C dn . Capacity retention rate = Discharge specific capacity after n cycles (C dn ) / Initial cycle discharge specific capacity (C d1 ).
[0221] The results are shown in Table 3.
[0222] (4) Full cell capacity retention rate at 45 °C
[0223] At 45 °C, charge at a constant current of 1C to 4.25V, then charge at a constant voltage of 4.25V until the current drops to 0.05C, and then discharge at a constant current of 1C to 2.8V to obtain the initial cycle discharge specific capacity (C d1 ); Repeat the charge and discharge process until the 300th cycle. The discharge specific capacity of the lithium-ion battery after n cycles is denoted as C dn . Capacity retention rate = Discharge specific capacity after n cycles (C dn ) / Initial cycle discharge specific capacity (C d1 ).
[0224] The results are shown in Table 3.
[0225] (5) Full cell swelling test at 70 °C
[0226] Store the full cell at 70 °C in a 100% charged state (SOC). Measure the open circuit voltage (OCV) and AC internal resistance (IMP) of the cell before, during, and after storage to monitor the SOC, and measure the volume of the cell. Among them, take out the full cell every 48h of storage, let it stand for 1h and then test the OCV and IMP, and measure the volume of the cell by the drainage method after cooling to room temperature. The drainage method is to first measure the gravity F1 of the cell alone with a balance that automatically converts the unit of the dial data, and then place the cell completely in deionized water (density known to be 1g / cm 3 ), measure the gravity F2 of the cell at this time. The buoyancy F_float of the cell is F1 - F2, and then according to Archimedes' principle F_float = ρgV_drain, calculate the volume of the cell V = (F1 - F2) / ρg.
[0227] After each volume test, recharge the cell. Charge at a constant current of 1C to 4.25V, then charge at a constant voltage of 4.25V until the current drops to 0.05C. After the recharge is completed, put it back into the furnace for continued testing.
[0228] After 30 days of storage, the volume of the battery cells was measured, and the increase in the volume of the battery cells after storage relative to the volume of the battery cells before storage, i.e., the gas production, was calculated.
[0229] See Table 3 for the results.
[0230]
[0231]
[0232]
[0233] From the results in Tables 1 to 3, it can be seen that compared with Comparative Example 1, on the one hand, the positive electrode active material of the present application has a high compaction density, so that the battery has a high energy density; on the other hand, the positive electrode active material of the present application has a lithium-rich layer structure, which can maintain excellent structural stability during the charge and discharge process, effectively reduce the degree of lithium-nickel mixing, effectively prevent the electrolyte from having side reactions on the surface of the positive electrode active material, reduce oxygen release, and greatly improve the cycle performance and safety performance of the battery. In addition, a coating Li is formed on the surface of the positive electrode active material of the present application. e CoO2 can further effectively prevent the electrolyte from undergoing side reactions on the surface of the positive electrode active material, thereby further improving the cycle performance and safety performance of the battery.
[0234] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, characterized in that: The chemical formula of the positive electrode active material is Li 1+a [Ni x Co y Mn z M1 b M2 c O2, where 0.05 < a < 0.5, 1 / 3 ≤ x < 1, 0 ≤ y < 1 / 3, 0 ≤ z < 1 / 3, 0 < b < 0.1, 0 < c < 0.1, x + y + z + b + c = 1, M1 is one or more elements selected from Mo, Zr, W, Sb, Nb, Te, and Ga, and M2 is one or more elements selected from Mg, Al, Ca, and Ti. The positive electrode active material is in the shape of particles, including a lithium-rich layer extending from the particle surface to the inside of the particle. In a single particle of the positive electrode active material, on a cross section passing through the geometric center of the particle, the ratio of the average Li element content per unit area in the lithium-rich layer to the average Li element content per unit area in the non-lithium-rich layer is greater than 1:1 and less than or equal to 1.5:
1.
2. The positive electrode active material according to claim 1, characterized in that In a single particle of the positive electrode active material, on a cross section passing through the geometric center of the particle, the ratio of the average Li element content per unit area in the lithium-rich layer to the average Li element content per unit area in the non-lithium-rich layer is (1.05-1.2):
1.
3. The positive electrode active material according to claim 1, characterized in that 0.1 <a<0.2,0.6≤x<1。 4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The positive electrode active material satisfies: k=2t / Dv50, and k is greater than 0 to 0.6, wherein t is the thickness of the lithium-rich layer extending from the particle surface of the positive electrode active material to the interior of the particle, and Dv50 is the particle size corresponding to when the volume cumulative distribution percentage of the positive electrode active material reaches 50%.
5. The positive electrode active material according to claim 4, characterized in that k is 0.01 to 0.
3.
6. The positive electrode active material according to claim 4, characterized in that The Dv50 of the positive electrode active material is 5-15 μm.
7. The positive electrode active material according to claim 6, characterized in that The Dv50 of the positive electrode active material is 8-10 μm.
8. The positive electrode active material according to claim 4, characterized in that The lithium-nickel mixing degree of the positive electrode active material is ≤5%.
9. The positive electrode active material according to claim 8, characterized in that The lithium-nickel mixing degree of the positive electrode active material is ≤3%.
10. The positive electrode active material according to claim 4, characterized in that The weight ratio of the M1 element to the M2 element in the positive electrode active material is 1:0.1-1:
1.
11. The positive electrode active material according to claim 10, characterized in that The weight ratio of the M1 element to the M2 element in the positive electrode active material is 1:0.1-1:0.
5.
12. The positive electrode active material according to claim 4, characterized in that The positive electrode active material further has a coating, the chemical formula of which is Li e CoO2, of which 0 <e≤1。 13. The positive electrode active material according to claim 12, characterized in that: The coating has a thickness of 0.01-0.2 μm.
14. The positive electrode active material according to claim 13, characterized in that The coating has a thickness of 0.05-0.1 μm.
15. The positive electrode active material according to any one of claims 12 to 14, characterized in that The weight ratio of the coating to the positive electrode active material is (0.002-0.02):
1.
16. The positive electrode active material according to claim 15, characterized in that The weight ratio of the coating to the positive electrode active material is (0.005-0.012):
1.
17. The positive electrode active material according to claim 4, characterized in that The (Dv90-Dv10) / Dv50 of the positive electrode active material is ≥1.
1.
18. The positive electrode active material according to claim 17, characterized in that The (Dv90-Dv10) / Dv50 of the positive electrode active material is ≥1.
2.
19. The positive electrode active material according to claim 4, characterized in that: The positive electrode active material is 5000kg / 1.33cm 2 The compaction density under pressure is ≥3.4g / cm 3 .
20. A method for preparing a positive electrode active material, characterized in that: The method comprises the following steps: S1) co-heating a precursor of a positive electrode active material and a lithium source at low temperature to obtain a mixture, mixing the mixture, a compound containing an M1 element, and a compound containing an M2 element, and sintering to obtain a matrix material; S2) adding the matrix material obtained in step S1) into an aqueous solution containing a soluble Co-containing compound and a soluble Li-containing compound, washing, filtering, and drying to obtain a positive electrode active material; Wherein, in the step S1), the temperature of the low-temperature co-heating is 150-400°C and the time is 1-6h. The chemical formula of the positive electrode active material is Li 1+a [Ni x Co y Mn z M1 b M2 c O2, where 0.05 < a < 0.5, 1 / 3 ≤ x < 1, 0 ≤ y < 1 / 3, 0 ≤ z < 1 / 3, 0 < b < 0.1, 0 < c < 0.1, x + y + z + b + c = 1, M1 is one or more elements selected from Mo, Zr, W, Sb, Nb, Te, and Ga, and M2 is one or more elements selected from Mg, Al, Ca, and Ti. The positive electrode active material is in the shape of particles, including a lithium-rich layer extending from the particle surface to the inside of the particle. In a single particle of the positive electrode active material, on a cross section passing through the geometric center of the particle, the ratio of the average Li element content per unit area in the lithium-rich layer to the average Li element content per unit area in the non-lithium-rich layer is greater than 1:1 and less than or equal to 1.5:
1.
21. The method for preparing a positive electrode active material according to claim 20, characterized in that: In a single particle of the positive electrode active material, on a cross section passing through the geometric center of the particle, the ratio of the average Li element content per unit area in the lithium-rich layer to the average Li element content per unit area in the non-lithium-rich layer is (1.05-1.2):
1.
22. The method for preparing a positive electrode active material according to claim 20, characterized in that: 0.1 <a<0.2,0.6≤x<1。 23. The method for preparing a positive electrode active material according to any one of claims 20 to 22, characterized in that: In the step S1), the temperature of the low-temperature co-heating is 200-300° C. and the time is 2-4 hours.
24. The method for preparing a positive electrode active material according to claim 23, characterized in that: In the step S1), the molar ratio of the Li element in the lithium source to the metal element in the precursor of the positive electrode active material is 1.2-1.5, the metal elements are Ni, Co and Mn, the sintering temperature is 600-850°C, the sintering time is 9-12h, and the sintering atmosphere is air or oxygen.
25. The method for preparing a positive electrode active material according to claim 24, characterized in that: In the step S1), the molar ratio of the Li element in the lithium source to the metal element in the precursor of the positive electrode active material is 1.25-1.4, and the sintering atmosphere is oxygen.
26. The method for preparing a positive electrode active material according to claim 23, characterized in that: In the step S1), the compound containing the M1 element is one or more of an oxide, hydroxide, carbonate, oxalate or nitrate containing the M1 element, and the amount of the M1 element added in the step S1) is 2000-5000 ppm, based on the weight of the precursor of the positive electrode active material; The compound containing the M2 element is one or more of an oxide, hydroxide, carbonate, oxalate or nitrate containing the M2 element. The amount of the M2 element added in the step S1) is 200-2000 ppm, based on the weight of the precursor of the positive electrode active material.
27. The method for preparing a positive electrode active material according to claim 26, characterized in that: In the step S1), the amount of the added M1 element is 3000-4000 ppm, and the amount of the added M2 element is 400-1000 ppm, based on the weight of the precursor of the positive electrode active material.
28. The method for preparing a positive electrode active material according to claim 23, characterized in that: In step S2), the soluble Co-containing compound is selected from one or more of Co(CH3COO)2, CoC2O4, CoSO4, Co(NO3)2 and CoCl2, and the amount of Co element added in step S2) is 1000-20000 ppm, based on the weight of the precursor of the positive electrode active material; the soluble Li-containing compound is selected from one or more of Li2SO4, LiNO3, LiC2O4, CH3COOLi and LiCl, and the amount of Li element added in step S2) is 500-5000 ppm, based on the weight of the precursor of the positive electrode active material.
29. The method for preparing a positive electrode active material according to claim 28, characterized in that: In the step S2), the amount of the Co element added is 5000-13000 ppm, and the amount of the Li element added in the step S2) is 1000-1500 ppm, based on the weight of the precursor of the positive electrode active material.
30. The method for preparing a positive electrode active material according to claim 23, characterized in that: In step S2), the water washing temperature is 0-100° C., and the water washing time is 1-30 min.
31. The method for preparing a positive electrode active material according to claim 30, characterized in that: In the step S2), the water washing temperature is 5-50° C., and the water washing time is 2-5 min.
32. The method for preparing a positive electrode active material according to claim 23, characterized in that: In step S2), the drying is vacuum drying, and the drying temperature is 40-120° C., and the drying time is 6-24 hours.
33. The method for preparing a positive electrode active material according to claim 32, characterized in that: In the step S2), the drying temperature is 80-100° C., and the drying time is 12-18 hours.
34. The method for preparing a positive electrode active material according to claim 23, characterized in that: In the step S1), the lithium source is selected from at least one of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4 and CH3COOLi.
35. The method for preparing a positive electrode active material according to claim 34, characterized in that: In the step S1), the lithium source is selected from at least one of LiOH·H2O, Li2SO4 and LiNO3.
36. The method for preparing a positive electrode active material according to claim 23, characterized in that: The method further comprises step S3): mixing the positive electrode active material obtained in step S2) with a Co-containing compound and a Li-containing compound, sintering at a temperature of 500-800° C. for 5-15 hours in an air or O2 atmosphere to obtain a positive electrode active material having a coating, wherein the chemical formula of the coating is Li e CoO2, of which 0 <e≤1。 37. The method for preparing a positive electrode active material according to claim 36, characterized in that: In step S3), the sintering temperature is 550-750° C. and the sintering time is 5-10 h.
38. The method for preparing a positive electrode active material according to claim 36 or 37, characterized in that: In the step S3), the Co-containing compound is selected from at least one of Co3O4, Co(OH)2, CoO, CoOOH, Co(CH3COO)2, CoC2O4 and CoCO3, the Dv50 of the Co-containing compound particles is 0.001-10 μm, and the amount of the Co element added in the step S3) is 500-20000 ppm, based on the weight of the precursor of the positive electrode active material; The Li-containing compound is selected from at least one of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4 and CH3COOLi, the Dv50 of the Li-containing compound particles is 0.001-1μm, and the amount of Li element added in the step S3) is 100-3000ppm, based on the weight of the precursor of the positive electrode active material.
39. The method for preparing a positive electrode active material according to claim 38, characterized in that: In the step S3), the Dv50 of the Co-containing compound particles is 0.001-1 μm, and the amount of the Co element added in the step S3) is 2000-15000 ppm, based on the weight of the precursor of the positive electrode active material; The Dv50 of the Li-containing compound particles is 0.01-0.05 μm, and the amount of the Li element added in the step S3) is 500-1500 ppm, based on the weight of the precursor of the positive electrode active material.
40. A secondary battery, characterized in that: The secondary battery comprises the positive electrode active material according to any one of claims 1 to 19 or the positive electrode active material prepared by the method according to any one of claims 20 to 39.
41. An electrical device, characterized in that: Includes the secondary battery as described in claim 40.
Citation Information
Patent Citations
High-compaction-density positive electrode material and electrochemical energy storage device
CN111384372A
Two-phase positive electrode material for lithium battery and method for the synthesis of same
CN103403929A
Lithium-defect high-nickel lithium-rich layered material and preparation method thereof
CN114843495A